Evaluation of bone tissue remodeling and mineral metabolism in elderly patients who have not been previously examined and have received no antiosteoporotic therapy - S B Malichenko; Elena Aleksandrovna Mashchenko; E R Shakhnis; M U Shibilova; V S Malichenko (Современная ревматология)
Objective: to evaluate bone tissue remodeling and mineral metabolism in elderly women who have not been previously examined and have received no antiosteoporotic therapy. Patients and methods. A total of 3152 women aged 65—75 years were examined using questionnaires and tests according to international validated scales and tests. The investigators measured bone density by dual-energy X-ray absorptiometry and mineral and bone mineral parameters. Results. Most patients were ascertained to have motor and physical impairments and cognitive dysfunction; 100% of cases had risk factors for osteoporosis (OP); 32.4% had a history of atraumatic fractures; 56.4% were diagnosed as having OP during standard examinations; 72.7% needed treatment in accordance with the FRAX procedure. The sensitivity of FRAX in patients (with OP without pathological fractures, OP with a history of low-energy fractures, or osteopenia with pathological fractures) requiring treatment according to these standard methods was 70.3, 71.5, and 24.3%, respectively. Conclusion. The majority of elderly (65—75-year-old) women who had not been previously examined and had received no antiosteoporotic therapy were found to have bone metabolic disturbances, a history of fractures in the presence of cognitive dysfunction, impaired motor activity, lowered quality of life, and inadequate calcium intake. At the same time, FRAX is not always the method of choice.